Cycling as a food-delivery rider. Or the difficult negotiation among speed, safety and accuracy - Francesco Bonifacio (SHARE Press, 2022)
Platform-based food-delivery riders have been primarily analyzed in relation to organisational or regulatory issues, thus overlooking the actual practices that involve them materially, bodily and cognitively. In particular, less attention has been given to a central aspect of this occupation: cycling. By understanding food-delivery work as a social practice (Hui et al., 2016), this paper aims to show that: 1) the organisational and material conditions in which food-delivery work takes place frame the emergence of a specific mode of urban cycling, which concerns the difficult negotiation of speed, safety and accuracy. 2) in order to meet the requirements of practice, riders draw on a set of norms and practical skills by which they define the correct way to accomplish this work. The research draws on a seven-months Milan-based observant participation (Wacquant, 2015) - during which the author worked as a Glovo part-time rider - supplemented by 21 in-depth interviews with workers.